The effect of simultaneous prompting on teacher OTRs and student behavior. Issue 1 (2nd November 2020) - Haydon, Todd; Musti-Rao, Shobana; Kennedy, Alana M.; Dillon, Cara
Abstract: In this study researchers examined a teacher's use of simultaneous prompting (SP) procedure in a fourth- grade special education classroom setting. Using an ABAB single subject design, the effects of a SP procedure on an increased rate of delivering questions with a small group of students identified with emotional behavior disorders were examined. Results indicated that when the teacher increased the rates of opportunities to respond (OTR), the students' on-task behavior, rate of correct responses increased, and number of errors decreased. A discussion of limitations and future research directions is included.